Characteristics and Clinical Managements of Chronic Skin Ulcers Based on Traditional Chinese Medicine. (14th May 2012) - Li, Fu-Lun; Wang, Yi-Fei; Li, Xin; Li, Feng; Xu, Rong; Chen, Jie; Geng, Lin; Li, Bin
Abstract : Chronic skin ulcer (CSU), including diabetic ulcers, venous ulcers, radiation ulcers, and pressure ulcers, remains a great challenge in the clinic. CSU seriously affects the quality of life of patients and requires long-term dedicated care, causing immense socioeconomic costs. CSU can cause the loss of the integrity of large portions of the skin, even leading to morbidity and mortality. Chinese doctors have used traditional Chinese medicine (TCM) for the treatment of CSU for many years and have accumulated much experience in clinical practice by combining systemic regulation and tropical treatment of CSU. Here, we discuss the classification and pathogenic process of CSU and strategies of TCM for the intervention of CSU, according to the theories of TCM. Particularly, we describe the potential intervenient strategies of the "qing-hua-bu" protocol with dynamic and combinational TCM therapies for different syndromes of CSU.